Why apply for an intercalated research degree? - Agha, Riaz (Int J Surg Oncol (N Y), 2017)
Intercalated degrees are commonly undertaken as part of the medical undergraduate course. In this article, we discuss the advantages and disadvantages of intercalation, along with alternatives that could be considered.